SOSIALISASI DAN PELATIHAN PERAKITAN KOMPUTER PADA PONDOK PESANTREN NAFIDATUNNAJAH - Dani; A. Nurul Anwar; Saprudin (Abdi Jurnal Publikasi, 2024)
The training carried out at the Nafidatunnajah Islamic Boarding School is part of the obligations of community service college tridharma lecturers in understanding computer assembly for students at the Nafidatunnajah Islamic boarding school in installing computer hardware and software, where the quality of the students greatly influences the human resources that can used as a benchmark in assembly mastery. As is known, the Nafidatunnajah Islamic Boarding School has a vision and mission to form students with noble character, discipline, intelligence, character and insight into science and technology education. As well as the mission of performing the five daily prayers on time, educating students to appreciate and respect each other, implementing a clean heart, mind, speech and environment, developing students' potential through creative education. And the human resources section for students is a benchmark for students in knowing or understanding the main parts of a computer. The computer assembly training activities are presented in the form of explanations, video showings, discussions and practice in the field. The benefits obtained from this activity include being able to assemble computers and computer parts, so that students can have skills in the field of computer assembly and can master proper assembly techniques. This shows that the students are very proficient in knowing hardware and software, so that in the future the students will be used as capital in getting jobs or independent businesses.